PEMETAAN EPITOP DAN APLIKASI KLINISNYA - Jusak Nugraha (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Epitope mapping is one of the important findings in immunoIogy. The idea of systematic epitope mapping was first described byGeysen et al (Geysen et al., 1987a,b). This technic is further developed together with other important findings such as monoclonalantibody production, DNA recombinant, peptide synthesis and phage display of peptide or protein. The usage of this technic is to know theexact binding site of antigen with antibody or T cell receptor, and can be used as the basic information to design a vaccine or diagnostictools. The term epitope can be further classified as functional epitope, structural epitope, binding epitope, protective epitope, heavyinfection epitope, neutralization epitope etc. In this article will be reviewed topics about epitope: B and T cell epitope mapping technicsusing synthetic pin and its application.